Toward a Bakhtinian typology of ambient advertising - Karimova, Gulnara Z. (Routledge info@tandf.co.uk, 2014)
Ambient advertising represents a growing sector of creative advertising practice, but has garnered little academic research. This paper aims to provide a theoretical foundation for the examination of ambient advertising's place within the marketing communication mix. The author presents a typology of ambient advertising based on the theory of the chronotope by Mikhail Bakhtin (1895-1975), the creative expression of the intersection between temporal and spatial dimensions, arguing that this represents the most fecund model for exploring the way in which ambient advertising seeks to harness the matrix of time and place. The typology offers a rationale for comparing different ambient campaigns on the basis of the degree to which they clearly express a particular chronotope and goes on to link this to a consideration of rhetorical persuasiveness. © 2012 © 2012 Taylor & Francis.
Keywords: ambient advertising; Bakhtin; space/time; typology